Waste Polyurethane Reinforced Polyester Composite, Production and Characterization - Demirel, Maruf Hurşit; Aydoğmuş, Ercan (Turkish Chemical Society, 2022)
In this research, new composite materials were improved by reinforcing the environment-polluting waste polyurethane (WPU) to unsaturated polyester (UP). Polyester composites were produced with WPU, UP, methyl ethyl ketone peroxide (MEKP), and cobalt octoate (Co. Oc.). The effect of WPU on the changes in density, Shore D hardness, thermal conductivity coefficient, thermal stability, and porosity of the obtained composites were investigated. According to the findings, as WPU ratio increased in the composite, both the thermal conductivity coefficient and the density of the composite decreased. Shore D hardness was been found to decrease as the rate of WPU in polyester composites raised. The use of optimum WPU ratios (7 wt.%) in composite production improved some thermo-physical properties of polyester composite. The high use of WPU negatively affected both the surface morphology and thermal stability of the polyester composite. In addition, the parameters affecting the production of polyester composites were optimized according to response surface methodology (RSM). © 2022, Russian Academy of Sciences. All rights reserved.
Keywords: density; Polyester composite; Shore D hardness; thermal conductivity